Analisis Empiris Transformasi Dig Pengaruh Kualitas Layanan, Kepercayaan, dan Kemudahan Aplikasi terhadap Loyalitas Pengguna Mobile Banking pada Bank Daerah - Januar Akbar; Siti Jamilah; Muhaedi Muhaedi (JURNAL ECONETICA: Jurnal Sosial, Ekonomi, dan Bisnis, 2025)
This study aims to analyze the influence of service quality, trust, and ease of use on mobile banking user loyalty at a regional bank. The background of this study is based on the increasing role of digital services in the banking industry and the importance of user loyalty as an indicator of service success. This study used a quantitative approach with an explanatory research method. Data were collected through questionnaires distributed to 150 respondents who were active mobile banking users at regional banks using a purposive sampling technique. Data analysis was performed using multiple linear regression after undergoing validity, reliability, and classical assumption tests. The results showed that service quality, trust, and ease of use of the application had a positive and significant influence on user loyalty, both partially and simultaneously. Service quality was the most dominant factor influencing loyalty, followed by trust and ease of use. These findings suggest that improving service quality, including speed, security, and responsiveness, as well as strengthening trust and ease of use of the application, can significantly increase mobile banking user loyalty. This study provides a theoretical contribution to the development of literature related to user behavior of digital banking services and provides practical implications for regional banks in designing strategies to improve service quality. By managing these three key factors in an integrated manner, regional banks can sustainably increase user satisfaction and loyalty.